New Urban Narratives and the New European Bauhaus - Kubicki, Paweł (Porównania, 2024)
This article deals with the issue of urban narratives in times of major changes. European cities developed in the process of the long term (longue durée), their physical fabric changing and adapting to the requirements of subsequent epochs, therefore creating a specific urban palimpsest. Every change, however, needs legitimacy and new stories that allow the urban palimpsest to be read in a new context. It has to provide narratives through which the identity of the city is preserved, despite its constant transformation. This article focuses on analyses of new urban narratives that supplant narratives relating to the city of the modern (Fordist) era. New urban policies, especially those developed as part of the “New European Bauhaus” project initiated by the European Commission, play an important role in this process. Every major change provokes social resistance, and in this case we can observe the creation of alternative urban narratives, shaped by social movements of a backlash or new Luddism character.